2007
DOI: 10.1152/ajpheart.01115.2006
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid receptor activation before ischemia reduces gap junction permeability in ischemic myocardium by PKC-ε-mediated phosphorylation of connexin 43

Abstract: .-The aim of this study was to examine the hypothesis that ␦-opioid receptor activation before ischemia suppresses gap junction (GJ) permeability by PKC-mediated connexin 43 (Cx43) modulation, which contributes to infarct size limitation afforded by the ␦-opioid receptor activation. A ␦-opioid receptor agonist, [D-Ala 2 ,D-Leu 5 ]-enkephalin acetate (DADLE, 300 nM), was used in place of preconditioning (PC) ischemia to trigger PC mechanisms in rat hearts. GJ permeability during ischemia, which was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 35 publications
10
47
1
Order By: Relevance
“…7 On the other hand, an excess of [Ca 2+ ]i causes GJ channel closure. 37 Consistent with a previous report in perfused rat heart, 38 in the present study GJs were functional in 30 min of ischemia as demonstrated by dye transfer assay. We conclude that brief ischemia enhances translocation of Cx43 to GJs, leading to GJIC enhancement and CBN spread in the risk area, whereas the non-risk area has low GJIC activity and no spread of CBN after reperfusion.…”
Section: Involvement Of Gjic In Spread Of Cbn and Infarct Developmentsupporting
confidence: 93%
“…7 On the other hand, an excess of [Ca 2+ ]i causes GJ channel closure. 37 Consistent with a previous report in perfused rat heart, 38 in the present study GJs were functional in 30 min of ischemia as demonstrated by dye transfer assay. We conclude that brief ischemia enhances translocation of Cx43 to GJs, leading to GJIC enhancement and CBN spread in the risk area, whereas the non-risk area has low GJIC activity and no spread of CBN after reperfusion.…”
Section: Involvement Of Gjic In Spread Of Cbn and Infarct Developmentsupporting
confidence: 93%
“…Unlike PKCδ, the function of PKCα at cell-cell junctions is thought to modulate desmosomal adhesion of epithelial cells in response to wounding (Wallis et al, 2000) and to increase endothelial permeability by the disruption of VE-cadherin junctions (Sandoval et al, 2001). As for PKCε, this has been shown to reduce gap junction permeability (Doble et al, 2000;Miura et al, 2007), weaken tight junctions (D'Souza et al, 2007) and suppress adherens junctions (Imamdi et al, 2004). PKCγ was recently reported to have a role in the regulation of gap junctions (Akoyev and Takemoto, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…27 Phosphorylation of Cx43 by PKCε plays a crucial role in δ-opioid-induced suppression of GJ permeability in ischemic myocardium. 28 During the late phase of EP, PKCε did not translocate to intercalated disks, but myocardial injury was still significantly attenuated, as it was during the early phase of EP. The cause of this might be related to PKCε phosphorylation.…”
Section: Early and Late Cardioprotective Effect Of Ep Against Exhaustmentioning
confidence: 93%